Mechanisms of Aβ Clearance and Degradation by Glial Cells - Ries, Miriam; Sastre, Magdalena (Frontiers in Aging Neuroscience, 2016)
Glial cells have a variety of functions in the brain, ranging from immune defence against external and endogenous hazardous stimuli, regulation of synaptic formation, calcium homeostasis, and metabolic support for neurons. Their dysregulation can contribute to the development of neurodegenerative disorders, including Alzheimer’s disease (AD). One of the most important functions of glial cells in AD is the regulation of Aβ levels in the brain. Microglia and astrocytes have been reported to play a central role as moderators of Aβ clearance and degradation. The mechanisms of Aβ degradation by glial cells include the production of proteases, including neprilysin, the insulin degrading enzyme (IDE), and the endothelin-converting enzymes, able to hydrolyse Aβ at different cleavage sites. Besides these enzymes, other proteases have been described to have some role in Aβ elimination, such as plasminogen activators, angiotensin-converting enzyme, and matrix metalloproteinases. Other relevant mediators that are released by glial cells are extracellular chaperones, involved in the clearance of Aβ alone or in association with receptors/transporters that facilitate their exit to the blood circulation. These include apolipoproteins, α2macroglobulin, and α1-antichymotrypsin. Finally, astrocytes and microglia have an essential role in phagocytosing Aβ, in many cases via a number of receptors that are expressed on their surface. In this review we examine all of these mechanisms, providing an update on the latest research in this field.